2021
DOI: 10.1111/hel.12830
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of antibiotics and vonoprazan for the treatment of Helicobacter pylori infections—Exploratory study

Abstract: Background Vonoprazan fumarate is a novel potassium‐competitive acid blocker more effective in suppressing acid production than proton pump inhibitors (PPIs) and when combined with antibiotics has been used to eradicate Helicobacter pylori (H. pylori) infection. However, it has not yet been examined in an Australian setting. This study aimed to report on the efficacy and safety of vonoprazan‐containing antibiotic combination therapies in the eradication of H. pylori. Methods A single‐center, exploratory, clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 46 publications
0
19
0
1
Order By: Relevance
“…In Korea, 12 H. pylori ‐positive patients received bismuth‐containing quadruple therapy with VPZ (bismuth 220 mg, clarithromycin 500 mg, amoxicillin 1000 mg, and VPZ 20 mg given twice daily) for 14 days; all were H. pylori ‐negative after treatment 20 . A single‐center, exploratory, clinical study 21 with 66 patients was conducted in Australia to evaluate the efficacy of VPZ therapy for treating H. pylori , the regimens included a number of different antibiotic combinations plus VPZ with or without bismuth for 10 days. The results showed that 97% eradication rate was achieved in the cohort of patients not lost to follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, 12 H. pylori ‐positive patients received bismuth‐containing quadruple therapy with VPZ (bismuth 220 mg, clarithromycin 500 mg, amoxicillin 1000 mg, and VPZ 20 mg given twice daily) for 14 days; all were H. pylori ‐negative after treatment 20 . A single‐center, exploratory, clinical study 21 with 66 patients was conducted in Australia to evaluate the efficacy of VPZ therapy for treating H. pylori , the regimens included a number of different antibiotic combinations plus VPZ with or without bismuth for 10 days. The results showed that 97% eradication rate was achieved in the cohort of patients not lost to follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the adverse effect of symptoms of bitterness in the mouth mainly appeared in the VAC group, which may have been caused by the side effects of clarithromycin. A study has reported that patients with VPZ-containing eradication regimens will have side effects of influenza-like symptoms such as chest pain, generalized pain, and dizziness ( 25 ). In this trial, patients with the same symptoms appeared in all 3 groups of regimens, and 2 patients in the L-VA group were discharged because of intolerable adverse effects, and influenza-like symptoms resolved after discontinuation of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the current estimate of resistance to regimens containing levofloxacin, metronidazole, and clarithromycin exceeds 30% in the United States (64); thus, the efficacy results used may overestimate current eradication rates with standard PPI use. However, substituting vonoprazan for PPI in various eradication regimens achieves greater efficacy with first-time treatment and results in eradication in over 90% among patients with a previous failed eradication attempt (65). Despite requiring more time and higher costs than an empirical approach, future pharmacoeconomic analyses should evaluate the impact of testing for resistance.…”
Section: Strengths and Limitationsmentioning
confidence: 99%